Technical-economic Analysis of Power Generation with Steam Cycles Fed with Residual Biomass from Rice and Corn - Rhenals-Julio, Jesus D.; Juan G. Castellar; Cesar A. Camargo; Mendoza, Jorge M. (International Journal of Energy Economics and Policy, 2023)
Technical and economic aspects for power generation based on residual biomass from rice and corn were evaluated in the department of Córdoba. The physicochemical characteristics of the biomass were determined as a blend for power generation using a conventional Rankine cycle with co-combustion, and the energy potential of the system and mass flows were determined through energy balances. Subsequently, thermodynamic analysis allowed establishing that the proposed system's efficiency is 24,4%. Regarding the effect of co-combustion in the process, it was found that increasing the fraction of rice husk in the mixture led to a reduction in net power production and an increase in cost. Finally, it was estimated that to achieve economic feasibility, a plant with a minimum of 20 MW and a generation cost of 0,172 USD/kWh is required.